Study of the Variability of the Physical and Mechanical Properties of Chinchilla Hair - Wafa Mahjoub; Albana Petrela; Jean-Yves Drean; Omar Harzallah (Journal of Natural Fibers)
This study investigates the physical and mechanical properties of Chinchilla hair, renowned for their softness, warmth, and lightweight qualities, obtained from Chinchilla rodents. The exploration of Chinchilla hair’s textile potential remains relatively scarce in literature, reflecting limited investigations into its properties. This study endeavors to analyze the physical and mechanical properties of the Chinchilla hair, considering various parameters such as type, sex, age, and anatomical position. Through meticulous categorization, we examined key attributes, including length, diameter, and mechanical properties, unveiling its remarkable potential for textile applications. Employing ANOVA statistical analysis, we demonstrated the significant influence of factors such as age and anatomical area on key parameters, including fiber diameter, length, and tenacity. Our study reveals that the impact of species on tenacity is contingent upon the sex of the chinchilla, while age-related changes may exhibit limited influence on hair strength.